Beauty as revealed in nature - McCurry, N. Ollie (My University, 1900)
Introduction: As we press forward in the eager search for knowledge and truth, seeking wisdom from the study and experience of the great scholars of the Medieval and present period; reaching out for the more complex things that we think must mould our lives and make us truer men and women, we are apt to miss some of the simpler things, which, if carefully studied, might benefit us most. Therefore, pause and view some of the first works of our Creator. Let us consider nature from our simple standpoint, and see what knowledge she holds in store. Everywhere in our land is heard the rustling of leaves, the sighing of the trees, and the low, melancholy moan of the mysterious wind, which bids us to ponder upon the wonderful things around us. The earth adorned in an enchanting robe, far and near, like gold encampments, reminds us of the precious coin for which men go to foreign lands and give up home, friends and their lives to possess. Our groves were God’s first temples, and it was here, beneath the pure skies, and the branches of the gray old trunks which mingle their boughs high in the heavens, that the humble worshipers first held communion with their maker; the trees of the forest rear a paradise upon the lonely plains, few places are found that are to dear for the song or chirp of the birds, and hardly a valley so desolate that a lily could not bloom therein.
Citation: McCurry, N. Ollie. Beauty as revealed in nature. Senior thesis, Kansas State Agricultural College, 1900.
Morse Department of Special Collections
Keywords: Nature; Humanity; Theses; Manuscripts (documents)